257 Effects of feeding different levels of quebracho (Schinopsis balansae) extract in a high-roughage total mixed ration on seasonal manure gas emissions. (5th December 2019) - Norris, Aaron B; Tedeschi, Luis O; Foster, Jamie L; Muir, James P; Pinchak, Bill E
Abstract: Our objective was to investigate how quebracho tannin (QT; Schinopsis balansae) fed at differing rates within a roughage-based diet affected manure gas emissions of growing steers. The utilization of ruminant species is required for efficient production of human-edible protein to meet global nutrient demands. However, gaseous byproducts from ruminant production systems, such as carbon dioxide (CO2 ), methane (CH4 ), and nitrous oxide (N2 O) are deleterious to the environment. It is estimated that CO2, CH4, and N2 O from managed waste and grazed lands account for roughly 54% of emissions from the livestock sector within the United States, with approximately 80% being associated with beef and dairy cattle. Supplementation of condensed tannins is a plausible method for improving environmental efficiency through the mitigation of enteric CH4 and shifting route of N excretion. During two experimental periods, 12 crossbred steers (236 ± 16 kg) were fed a roughage-based diet at maintenance level with the addition of QT at 0, 1.5, 3, and 4.5% of DM serving as dietary treatments. Following adaptation, feces were collected and gas fluxes measured using vented static chamber technique with manure incubated on the soil surface at two locations, College Station and Stephenville, during two periods corresponding to winter and spring. The daily flux of CO2 was influenced by soil moisture and temperature (r = 0.34; P < 0.01), whereas CH4 and N2 O were associated with soil moisture. Cumulative CO2 and gross CO2 equivalent (CO2 e) exhibited a dietary treatment effect at College Station (P ≤ 0.01), with a linear reduction with increased dietary QT. At both locations, we observed significance or tendencies for period effects for CO2, CH4, N2 O, and CO2 e (P ≤ 0.07) with period 2 having higher gas production. Within certain environments, QT supplementation could potentially reduce manure gas emissions, but additional investigation into animal variation is required.